Interval Pentapartitioned Neutrosophic Sets - Surapati Pramanik (Neutrosophic Sets and Systems, 2023)
Pentapartitioned neutrosophic set is a powerful mathematical tool, which is the extension of neutrosophic set and n-valued neutrosophic refined logic for better designing and modeling real-life problems. A generalization of the notion of pentapartitioned neutrosophic set is introduced. The new notion is called Interval Pentapartitioned Neutrosophic set (IPNS). Pentapartitioned neutrosophic set is developed by combining the pentapartitioned neutrosophic set and interval neutrosophic set. We define several set theoretic operations of IPNSs, namely, inclusion, complement, intersection. We also establish various properties of set-theoretic operators.